البعد الاجتماعي والسياسي في رواية لونجا والغول، لزهور ونيسي - أنموذجا - بلمهدي، نظيرة, مختاري، منى (جامعة الوادي University of Eloued, 2019)
يعد الأدب النسوي ظاهرة أدبية حديثة ترتكز على قضايا المرأة وظهر هذا الأدب في أحضان الحداثة ويعود ذلك إلى أسباب عدة منها ظهور الإستعمار الفرنسي ومن ضمن هذه القضايا رواية لونجا والغول ومنه نطرح التساؤل من هي لونجا والغول؟ درسنا في هذه الرواية البعد الإجتماعي والسياسي • الاجتماعي: - المرأة: وهي رمز الكفاح والنضال. - الحرية: تحقيق النصر بوسائل مختلفة. - التراث: الرجوع إلى تاريخ الأجداد • السياسي: يتمثل في: - التاريخ: تحرير معلومات تخص تاريخ الجزائر - السلطة: التهميش من طرف الإستعمار الغاشم. - الدولة: تمثلت في شخصية مليكة وهي رمز للدولة الجزائرية. - الإستعمار: أخذ إسم الغول وهو رمز للرعب والفزع والدمار • الرواية مثلت الواقع الاجتماعي والسياسي المرير وعبرت عن واقعها المأساوي وحاولت تغييره إلى الأحسن بطريقة مختلفة. The literature of women is a modern literary phenomenon based on women's issues and this literature appeared in the arms of modernity, due to several reasons, including the emergence of French colonialism, among which the story of Lunga and Ghoul, and ask the question of who is Lunga and Ghoul? In this novel we studied the social and political dimension • Social: - Women: a symbol of struggle and struggle. - Freedom: victory by different means. - Heritage: Back to the history of ancestors • Political: represented in: - Date: Edit information about the history of Algeria - Power: marginalization by the brutal colonization. - State: represented in the character of Malika, a symbol of the Algerian state. - Colonialism: taking the name of the Ghoul symbol of horror and horror and destruction • The novel represented the bitter social and political reality and expressed its tragic reality and tried to change it to the better in a different way.
Keywords: الاجتماعي، المرأة، الحرية، السياسي، التاريخ; Social, women, freedom, political, history